Software Engineering Development process, user interface design, methods and tools for Mobile Application Development - Raghavendra Rao, BG; Vasantha, S (International Journal of Computer Sciences and Engineering, 2025)
This paper provides an overview of important software engineering development process, user interface design tools, methods, application portability, quality and security, cost of development, hardware, software, licenses and developer accounts, proximity, Embrace minimalism.